Exploring tension and contradictions in youth's activity of painting graffiti. (September 2014) - Hedegaard, Mariane
Graffiti as writing and painting with spray cans in public spaces was recognised as a special youth movement in the 1960s and 1970s in New York City. From there, it spread to other metropolitan cities around the world. Through graffiti activity, young people positioned themselves in a youth movement that violates public spaces. This article focuses on the contradictions and tensions of being part of an illegal subculture and being recognised as painting art. The tensions will be analysed from the perspective of societal conditions as well as painters' experiences, drawing on literature about graffiti and an interview project with graffiti painters in Denmark. Psychological aspects of the young person's engagement are analysed using concepts from Vygotsky's theory of creativity and art. The analyses contribute to understanding what graffiti activity means for a group of young persons in their change of position from childhood to young adulthood, and to a differentiation of Vygotsky's theory of art.